ДИНАМІКА ВІКОВОЇ СТРУКТІРИ МІЖНАРОДНОГО ТУРИЗМУ В ЧЕРНІВЕЦЬКІЙ ОБЛАСТІ ПРОТЯГОМ 2005-2018 РОКІВ - Костащук, Володимир Іванович; Підгірна, Валентина Никифорівна (Чернівецький національний університет імені Юрія Федьковича, 2020)
В статті розкрито основні теоретико-методичні підходи щодо дослідження міжнародного туризму за різними віковими групами. Для оцінки розвитку міжнародних туристичних потоків у різних вікових групах пропонується використовувати коефіцієнт туристичної активності вікової групи. Проаналізовано динаміку формування i розвитку міжнародних туристичних потоків за різними віковими групами в межах Чернівецької області. The article reveals the main theoretical and methodological approaches to the study of international tourism by different age groups. To assess the development of international tourist flows by different age groups, it is proposed to use the coefficient of tourist activity of the age group. The dynamics of formation and development of international tourist flows by different age groups within Chernivtsi oblast is analyzed. Introduction. Tourism and recreation are currently one of the key sectors of the world economy. Their development depends on many factors, one of the key of which is the age structure. It is known that people of different ages have different tendencies to travel. One of the most mobile groups is the youth and older age groups. Presenting main material. One of the most important factors that significantly affect the development of international tourism is the age structure. The age structure of tourists has a significant impact on: 1) determining the types of tourist services provided to international tourists; 2) the potential cost of consumption of tourist services (the price of the tourist product). Currently, in the statistical study of the age structure of tourists in Ukraine, it is customary to distinguish 4 age groups: children (age range from birth to 14 years), adolescents (15-17 years), youth (18-28 years) and tourists over 29 years. This classification is based on a number of factors: physiological, psycho-emotional, socio-economic. However, a significant variance in the number of years during which the tourist belongs to a particular age group significantly affects the formation of the number of tourists. In order to determine the influence of age group on the development of tourism and taking into account the above aspects of such assessment, it is proposed to calculate the coefficient of age activity of tourists (σі). It is calculated as the ratio between the number of tourists per year of the age interval of the i-th age group (kі) to the average values of the number of tourists per 1 year of the age interval (kс). It is assumed that the population makes tourist trips throughout life, so it corresponds to the average life expectancy in the region. In tourism of Chernivtsi oblast, the highest indicators of age activity of tourists and their number per one year of the age interval are typical for adolescents (15-17 years) and older age groups (over 29 years). The average tourist activity of adolescents is 1.24 and for adults 1.23. This means that adolescents and older tourists are 24% more likely to travel than other age groups. Each of these groups is characterized by high rates of tourists for one year of the age interval – on average for adolescents, this figure is 1178.9 tourists, for the older age group – 1153.7 tourists. The leading positions of adolescents (despite the lowest absolute values) are explained primarily by the shortest duration of the age interval of this age group – 3 years, as well as a number of socio-economic factors. In particular, with reaching adolescence, the process of creating comfortable living conditions in families is mostly completed, parents succeed and income increases while reducing current expenses, so more money is allocated for adolescents for tourism and recreation. The latter factor is also crucial to explain the dominance of older tourists in the number of tourists. Conclusions. As a result of the study, a significant predominance in the age structure of tourists of older age groups in Chernivtsi oblast was revealed. The same age group is characterized by higher tourist activity, while children and young people have slightly lower rates of tourist activity. Socio-economic factors and processes have the greatest impact on tourist activity, because older age groups are characterized by a higher level of income, which creates favorable conditions for the intensification of tourist travel.
Dynamics of the age structure of international tourism in Chernivtsi oblast during 2005-2018.
Keywords: міжнародний туризм, туристична активність вікових груп, вікова структура туристів. international tourism, age group, tourist activity of age groups, age structure of tourists.